Effectiveness of behaviour change interventions to reduce the risk of faecal contamination in urban irrigated vegetable value chains – applying the COM-B behavioural framework - Galibourg, D.; Scott, R. E.; Gough, K. V.; Drechsel, Pay; Evans, B. E. (IWA Publishing, 2024)
In low- and middle-income countries, inadequate sanitation results in faecal contamination of the water used by urban farmers for irrigation. Consumers of raw contaminated vegetables run the risk of developing diarrhoeal diseases and helminth infections, which are a leading cause of under-five mortality and impact the well-being and productivity of millions of adults. This review identifies the evidence base for assessing which factors determine the success and/or failure of interventions that aim to manage the risk of faecal contamination in the urban irrigated vegetable value chain. We carried out a systematic search of the literature from the perspective of the COM-B behaviour framework (Capability þ Opportunity þ Motivation ¼ Behaviour). Our results reveal that most interventions address stakeholders’ opportunity or capability to adopt safe practices without adequately considering their motivation. Interventions often focus on one sector rather than on the whole value chain (sanitation, agriculture, trade, consumption). To effectively change hygiene and food safety practices in the urban irrigated vegetable value chain, stakeholders’ intrinsic motivations need to be identified. Where WHO’s multi-barrier approach is the best option, we recommend building on local multistakeholder platforms and adopting a behaviour change framework to support the largely technical change from farm to fork.